The Political Management of Consumer Credit Collateral in the Banking Industry. (2nd January 2020) - Schraten, Jürgen
ABSTRACT: Starting from Polanyi's notion of a 'counter movement' that becomes necessary due to the damaging of the social fabric by economic recklessness in a competitive market society, this article reveals a shift from an institutional towards a processual governance of the South African consumer credit market. During two critical moments of market development, responsible actors placed themselves in quasi-neutral positions of technical administrators. Between 1999 and 2006, they established large-scale institutions, which proved to be inapt for preventing over-indebtedness and rising inequality. Hence, they changed their strategy to precisely regulating the credit granting process on a local level after 2012. This did not reverse the tendency of increasing social inequality, but it shifted the focus of attention towards the individual decision-making of borrowers. It, therefore, contributed to securing a liberal market against interventionist economic ambitions.